135k views
20 votes
Derive

Sinxy = x² + 2xy​

User Thorntonc
by
5.1k points

1 Answer

6 votes

Answer:


(dy)/(dx) = (2x +2 y- ycosxy)/(x(cosxy-2))

Explanation:

Step(i):-

Given

sin xy = x² + 2xy ...(i)

Apply


(d)/(dx) UV = U^(l) V + U V^(l)


(d)/(dx) x^(n) = nx^(n-1)

Differentiating equation (i) with respective to 'x', we get


cosxy (d)/(dx) (xy) = 2x + 2( x(dy)/(dx) + y(1))


cosxy (x(dy)/(dx) +y(1)) = 2x + 2( x(dy)/(dx) + y(1))


cosxy (x(dy)/(dx)) + ycosxy = 2x + 2( x(dy)/(dx)) +2 y)


cosxy (x(dy)/(dx)) - 2( x(dy)/(dx)) = 2x +2 y- ycosxy


(cosxy-2) (x(dy)/(dx)) = 2x +2 y- ycosxy


(dy)/(dx) = (2x +2 y- ycosxy)/(x(cosxy-2))

User Pro Account
by
4.4k points